(untitled) (International Journal of Engineering and Computer Science, 2018)
Absence of any central co-ordination mechanism and shared wireless medium makes MANET more vulnerable to wide variety of attacks. In an internal attack, the attacker gains the normal access to the network and takes part in the network activities, either by some malicious impersonation to get the access to the network as a new node, or by directly compromising a current node and using it as a basis to conduct its malicious behaviors. In this paper, we developed an autonomous trust evaluation based cluster head misbehaviour detection and isolation in mobile ad hoc networks where the entire network is divided into hierarchical group of clusters, each cluster having a fully trusted Cluster Head (CH). As, CH, being an independent node that has mobility and autonomy behaviour, has the possibility that it may be vulnerable to DoS attacks. Hence, the assumption of CH being trusted cannot be considered. Therefore, ensuring the security of CH is essential which can be done by evaluating the trustworthiness of each CH. The trustworthiness of each CH is determined by its Group Leader (GL). In order to determine the cluster head and the group leader that are free from malicious attack, an autonomous trust evaluation is done for each CH to detect and isolate the misbehaving cluster head.